Analisis Kasus Penganiayaan BerdasarkanPasal 351KUHP (Studi Kasus Putusan Nomor 2/Pid.B/2019/PN.DPK) - Gilbert Immanuel Gultom; Tardip Panggabean; Erna Amalia (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
Based on Article 351 (Paragraph 1) of the Criminal Code on ordinary persecution where in this article persecution is divided into three parts, namely ordinary, mild and severe persecution as in the case that I took to make this thesis with case number 2/Pid.B/2019/PN. In this case, the panel of judges sentenced the perpetrator of persecution to 10 months imprisonment, while the sentence that should have been imposed on the perpetrator of ordinary persecution was 2 years and 8 months by considering various kinds of evidence and factors of persecution, This study aims to analyze cases of persecution that refer to Article 351 of the Criminal Code (KUHP) in Indonesia. In this analysis, we identify the elements necessary to determine whether an act can be classified as maltreatment under Article 351 of the Criminal Code. This research involves a case study and analysis of the Depok district court decision, as well as referring to applicable laws and regulations. The results of this analysis may provide a better understanding of the application of Article 351 of the Criminal Code in cases of maltreatment and its implications for the criminal justice system in Indonesia. Keywords: Maltreatment under Article 351 of the Penal Code